Effectiveness of Using Attractants to Control Hypothenemus hampei in Coffea arabica Crop in the Ecuadorian Amazon - Muñoz-Rengifo, Julio César; Alba Rojas, Jorge; Villamar-Torres, Ronald Oswaldo; Reyes-Pérez, Juan José; Mehdi Jazayeri, Seyed (AGRIVITA, Journal of Agricultural Science, 2021)
The present research was aimed to evaluate the effectiveness of attractants placed in craft traps to reduce the bit population (Hypothenemus hampei). Three different mixtures of attractants and control were used in craft traps (4 treatments, which represent the mixtures frequently used by Amazonian coffee growers), arranged in a completely random blocks design. The variable number adult coffee drill was analyzed, as well as the most economical and effective treatment in the capture of adult coffee bit. The data were processed by means of a variance analysis to determine the differences between treatments, and the Tukey media multiple comparison test, at the statistical significance of p<0.05. The results have confirmed that the use of craft traps is a good alternative for adult coffee bit control. The treatment that allowed a greater capture of the coffee bits was T1 (mixture of 2 liters of boiled water + 200 grams of ground coffee), this was also the treatment that had the lowest cost for the elaboration of the artisan trap ($ 14.30). Finally, T1 turned out to be the most effective treatment for adult coffee drill capture in Amazonian conditions of Ecuador.